Teacher Trainees’ Perception Of Their Lessons During Teaching Practice - Mohammad Nor, Faizah; Tumiran, Amir (2010)
This research is about the teacher trainees’ perception of their lessons during teaching practice. The purpose of this research is to investigate the perceptions of TESL teacher trainees on the effectiveness of the lesson they conducted during their teaching practice, the most frequent teaching method that was most employed during teaching practice and the technique that teacher trainees find most effective. For this purpose, a set of questionnaires were distributed to 26 third year TESL students who have done their teaching practice during their first semester. Data for this research was obtained through sets of questionnaires that were distributed by the end of their teaching practice period. The data was then analyzed qualitatively and quantitatively. The research findings indicate that the respondents was most likely to apply communicative base teaching whereby majority of the respondents agreed on using communicative language teaching as their main teaching principle in order to make their lesson more effective. At the end of this research, researcher found that the respondents choose communicative language teaching as their preferred teaching approach.